2020
DOI: 10.1021/acs.jpclett.0c00642
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Graphene Nitrene Two-Dimensional Catalyst Heterostructure Providing a Well-Defined Site Accommodating One to Three Metals, with Application to CO2 Reduction Electrocatalysis for the Two-Metal Case

Abstract: Recently, CO2 reduction to fuels has been the subject of great much numerous studies, but selectivity and activity remain inadequate. Progress has been made on single site twodimensional catalysts based on graphene coupled to a metal and nitrogen for CO2RR but the product is usually CO and the metal-N environment remains ambiguous. We report a novel 2D graphene-nitrene heterostructure (grafiN6) providing well-defined active sites (N6) that can bind 1 to 3 metals for CO2RR. We find that homo-bimetallic FeFe-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…The dual‐metal sites located adjacently on the same carbon substrate, which have been experimentally observed, could be regarded as a derivative structure of SACs. The Fe–Fe, [ 99 ] Fe–Cu, [ 100 ] and Ni–Co [ 101 ] based dual‐metal sites have been theoretically predicted to be active for electrochemical conversion of CO 2 into CO, HCOOH, CH 4 , and CH 3 CH 2 OH. The dual‐metal configurations can trigger unique synergetic interaction by tuning the electronic and geometric effects of active sites, which allows for alternative reaction paths to decrease the activation barriers of CO 2 RR.…”
Section: Carbon‐supported Sacs For Co2‐to‐co Conversionmentioning
confidence: 99%
“…The dual‐metal sites located adjacently on the same carbon substrate, which have been experimentally observed, could be regarded as a derivative structure of SACs. The Fe–Fe, [ 99 ] Fe–Cu, [ 100 ] and Ni–Co [ 101 ] based dual‐metal sites have been theoretically predicted to be active for electrochemical conversion of CO 2 into CO, HCOOH, CH 4 , and CH 3 CH 2 OH. The dual‐metal configurations can trigger unique synergetic interaction by tuning the electronic and geometric effects of active sites, which allows for alternative reaction paths to decrease the activation barriers of CO 2 RR.…”
Section: Carbon‐supported Sacs For Co2‐to‐co Conversionmentioning
confidence: 99%
“…[ 18 ] Beyond SACs, double‐atom catalysts (DACs), in which transition metal dimers are anchored in suitable substrates, have recently emerged as extended family members in catalytic field due to double active sites and the corresponding synergetic catalytic effect. [ 21–32 ] Experimentally, He et al. successfully synthesized the Fe dimer embedded in the graphene with adjacent single vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] To achieve an excellent double‐atom catalyst, we not only need suitable transition metal atoms, but also need to deliberately select an appropriate substrate that can firmly interact with the transition metal atoms. Numerous 2D materials [ 21–32 ] have been investigated as promising substrates after the successful synthesis of graphene in 2004. [ 33 ] Introducing vacancies and holes in pristine graphene can overcome the drawbacks of desorption and aggregation of transition metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…8a. Recently Chen et al [39], have indicated bimetallic graphene nitrene heterostructure FeFe-grafiN 6 systems as active sites for CO 2 reduction to multi-carbon products. The existence of this type of sites is also supported by our TEM analysis.…”
Section: Dynamics Of Fe Species On N-doped Graphene During Annealingmentioning
confidence: 99%